The powers of sound and song in early modern Paris - Hammond, Nicholas, 1963- (Perspectives on sensory history., 2019)
"An interpretation of early modern Paris demonstrating that sound was as important as vision during the reign of Louis XIV. Discloses myriad ways in which sound generated an interpenetration of elite and popular culture, revealing complex acoustic dimensions of class, politics, sexuality, and punishment"--